Implementation of Arduino Uno-Based Temperature Control for Drying Kandis Acid (Garcinia xanthochymus) - Ifmalinda Ifmalinda; Khandra Fahmi; Siska Dwi Putri (PERTETA, 2022)
Kandis acid is one of the spices that is often used for cooking and health ingredient. Processing kandis acid fruit skin is by the drying process. Drying can be done using tools or in the sun. Drying using tools is still not optimal because there is no temperature control during drying, this study drying was carried out using an arduino-based oven so that the initial temperature could be determined and the temperature during drying could be controlled. This study aims to evaluate the drying temperature control in an arduino uno-based oven and also to evaluate the drying method used on the quality of the kandis acid produced. Based on the research that has been done, controlling the drying temperature using an arduino uno-based oven that has been running well, the oven automatically controls the drying temperature to return to the set point temperature used (60 0C). The best quality of kandis acid is drying using a tool, seen from observations such as mold growth, drying time and drying rate. However, in drying using the sun, the value of vitamin C has a higher value than drying using a tool. The rind of the kandis acid used was 2,7 kg in each drying, the initial moisture content in drying using a tool was 83,289% with a final moisture content of 9,672% and the initial moisture content drying using sunlight was 83,744% with a final moisture content of 10,796%. The drying time for drying using a tool is 9,3 hours with a drying rate of 0,041 kg/hour, while for drying using sunlight was 20,7 hours with a drying rate of 0,036 kg/hour.